2012
DOI: 10.1088/0026-1394/49/1a/01003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Josephson voltage standards of the CMI and the BIPM (part of the ongoing BIPM key comparison BIPM.EM-K10.b)

Abstract: A comparison of the 10 V Josephson array voltage standard of the Bureau International des Poids et Mesures (BIPM) was made with that of the Czech Metrology Institute (CMI), Czech Republic, in February 2011. For this exercise, option B of the comparison protocol was applied for the nominal voltage of 10 V. The BIPM provided a reference voltage for measurement by the CMI using its Josephson standard with its own measuring device (option B of the comparison protocol). The final results are in good agreement withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…If the array is connected to an 'isolation ground' in the bias supply, this point must not be inadvertently connected to ground where it can add a significant systematic error [17,18]. To reduce the coupling effects between both standards, it has been demonstrated that biasing two arrays with only one dc bias source (the array to be compared naturally goes to within a few steps of the voltage provided by the reference array) provides a useful method of determining errors originating from ground loops [19].…”
Section: Ground Loopsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the array is connected to an 'isolation ground' in the bias supply, this point must not be inadvertently connected to ground where it can add a significant systematic error [17,18]. To reduce the coupling effects between both standards, it has been demonstrated that biasing two arrays with only one dc bias source (the array to be compared naturally goes to within a few steps of the voltage provided by the reference array) provides a useful method of determining errors originating from ground loops [19].…”
Section: Ground Loopsmentioning
confidence: 99%
“…The superconducting electrodes of the junctions are made of niobium and thus have to be operated below 9.1 K. Liquid helium is used as a cryogen in most apparatus, although some very good results have been obtained with cryocooler-based systems where the temperature set point can be higher than the equilibrium temperature of liquid helium [18,30]. For those JVSs, the array and its leads are permanently thermally anchored and therefore do not offer any flexibility for changing parameters such as in the 'floating mode' of the array from the ground potential or the change of the probe immersion to modify the RF signal propagation and/or thermal EMFs.…”
Section: Cryogenic Operating Temperature and Magnetic Shieldmentioning
confidence: 99%